2017
DOI: 10.5797/jnet.cr.2016-0133
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Mechanical Thrombectomy for Middle Cerebral Artery Occlusion with Trousseau Syndrome

Abstract: Objective and Case Presentation:The patient was an 86-year-old woman with histories of surgery for stomach, colon, and pancreatic cancers. In addition to left hemiparesis as a sequela of two past episodes of cerebral infarction, she newly developed right hemiplegia and acute cerebral infarction due to left middle cerebral artery (MCA) occlusion.Since the condition was not an indication for intravenous thrombolysis with recombinant tissue plasminogen activator (rt-PA), mechanical thrombectomy was immediately pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…3) There are now multiple reports of mechanical thrombectomy for Trousseau's syndrome; however, recurrent thrombectomy for stroke is uncommon. [3][4][5][7][8][9][10] In two large series, recurrent thrombosis was reported at about 2%, although not all of these received repeat intervention. 6,11) These series differ on their impression of the impact of recurrent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…3) There are now multiple reports of mechanical thrombectomy for Trousseau's syndrome; however, recurrent thrombectomy for stroke is uncommon. [3][4][5][7][8][9][10] In two large series, recurrent thrombosis was reported at about 2%, although not all of these received repeat intervention. 6,11) These series differ on their impression of the impact of recurrent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The present case is consistent with these characteristics. In cases where the prognosis is unfavorable because of terminal-stage cancer (3, 4), it is sometimes difficult to make a decision to undertake invasive surgery in patients in such poor condition. Recent article regarding endovascular therapy for cancer-related stroke revealed that the rate of good outcome at discharge was not significantly differ compared to those without cancer (5).…”
Section: Discussionmentioning
confidence: 99%
“…Four cases of thrombectomy for Trousseau syndrome have been reported. 6,9,10 More reports are available if tumor embolism is included, but none have described cases involving terminally ill patients. 22e24 Decision making in terminal care is very delicate and difficult.…”
Section: Commentmentioning
confidence: 99%
“…5 Trousseau syndrome is a common cause of ischemic stroke in cancer patients. 6 This syndrome was first reported by Armand Trousseau in 1865 and is characterized by hypercoagulation disorder in patients with malignancy. 7,8 This complication can markedly affect quality of life (QOL).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation